The improvement of drought tolerance in rice - Mohammed, Umar (2017)
The unpredictability of spatio-temporal drought patterns in the field and complexity of the physiological stress response mechanism involved have made it difficult to identify the essential traits for improved productivity under drought stress without compensating yield performance. (Serraj et al., 2011). Drought (severe water limitation) limits rice productivity, particularly in upland and rainfed systems which are prone to frequent drought and other abiotic stresses. Vulnerability in such areas is likely to worsen in the future. It is therefore critical to develop genetic improvement strategies to focus on improving productivity in such regions. The development of improved root system architecture, shoot morphology and whole plant physiological processes in order to generate drought tolerant rice cultivars It is in this context that this thesis used a multidisciplinary approach to improving drought tolerance in rice. One of the major phases was to study a diversity panel of African rice lines (Oryza sativa L) selected for being particularly well adapted to upland (aerobic) cultivation and was compared to a set of typical lowland (Asian in origin) cultivars. Plants were grown in plastic columns in expanded clay and exposed to temporary drought at key growth stages. In particular, the characterisation of these African accessions has improved our understanding of the interaction between photosynthetic response and how their roots interact with their environment and also in response to the above ground physiology. For example, a high leaf gas exchange CO2 assimilation, stomatal conductance and transpiration identified in two upland genotypes, N8 and N7 with high leaf water use efficiency as a result of a low stomatal conductance and high photosynthesis. The N8 also showed well-developed root system with significantly higher root depth and length, while the N7 has relatively higher central metaxylem area and higher stomatal density. A strong correlation was observed between root morphological properties (e.g. root average diameter, root length and root central metaxylem area) was observed, providing real evidence that optimal root morphology is needed to support high photosynthesis through increased water access and possibly higher hydraulic conductance across diverse genotypes.